1990
DOI: 10.1021/ie00104a020
|View full text |Cite
|
Sign up to set email alerts
|

Partition of carboxylic acids in an emulsion copolymerization system

Abstract: Reaction in the aqueous phase is often significant in emulsion polymerization systems that contain one or more water-soluble monomers. Accurate prediction of the partition of monomers between the aqueous, particle, and droplet phases is necessary for determining reaction rates, copolymer compositions, and surface properties of the latex particles. A model for predicting the partition of monomers between the various phases has been developed for an emulsion copolymer system.-A method for experimentally obtainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 9 publications
4
35
2
Order By: Relevance
“…Because MAA is the more hydrophobic of the two, it polymerizes inside the particles whereas the more hydrophilic AA Table I. tween the aqueous and particulate phases depends on the pH of the reaction environment. 6,34 A previous study showed that the partitioning of…”
Section: Ea4mentioning
confidence: 99%
See 1 more Smart Citation
“…Because MAA is the more hydrophobic of the two, it polymerizes inside the particles whereas the more hydrophilic AA Table I. tween the aqueous and particulate phases depends on the pH of the reaction environment. 6,34 A previous study showed that the partitioning of…”
Section: Ea4mentioning
confidence: 99%
“…34 The negative charge on the dissociated (anionic) form of MAA renders it more polar than these graphs. Given that the individual rate curves for MAA are similar at pH 2.2 and 4, it is the nondissociated form, and thus increases its relative attraction for other polar molecules such probably safe to say that at a pH lower than the pK a (pK a of MAA Å 4.36), 6 the rate of consump-as water and decreases its attraction for nonpolar species such as St or BA. Increasing the pH leads tion of MAA is independent of the pH.…”
Section: Ea4mentioning
confidence: 99%
“…As early as 1970s, Ceska have studied the carboxyl distribution in styrene (St)–butadiene copolymer latexes prepared in the presence of unsaturated acid monomers by neutron activation analysis and turbidimetric titration 18, 19. Subsequently, Shoaf and Poehlein investigated the partitioning of unsaturated acid monomers between St phase and aqueous phase and the kinetic behavior of emulsion copolymerization of St with unsaturated acid monomers 20–22. Okubo et al revealed the relationship between secondary nucleation and methacrylic acid (MAA) content in the emulsion copolymerization system of St and MAA 23.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1970s, Ceska studied the effect of carboxyl monomers on the particle formation and stabilization in soap-free emulsion polymerization [12,13]. Subsequently, Shoaf and Poehlein investigated the partitioning of carboxyl monomers between styrene and aqueous phase and the kinetic behavior of emulsion copolymerization with carboxyl monomers [14][15][16]. Moreover, the influences of carboxyl content and its distribution on particle morphology were also studied [9,17,18].…”
Section: Introductionmentioning
confidence: 99%